Evaluation of stover and grain in native corns in Guasave Sinaloa - Salinas-Vargas, Delfina; Maldonado-Peralta, María de los Ángeles; Rojas-García, Adelaido Rafael; Graciano-Obeso, Adalid; Ventura-Ríos, Joel; Maldonado-Peralta, Ramiro (Revista Mexicana de Ciencias Agrícolas, 2022)
Corn stover has always been used as a source of feed for cattle, goats, and sheep, although forage grasses have a series of benefits that increase the production of milk, meat and improve the reproductive efficiency of herds. The experiment was carried out with the objective of knowing the production of stover and grain yield in four native corns and two hybrids in Guasave, Sinaloa. Six genotypes of corn were used, four are native (yellow from Tlaxcala, blue from Oaxaca and red from Veracruz and white from Puebla) and two hybrids (4050 Dekalb® and Hipopótamo Asgrow®). The experimental design and treatments were established and analyzed in a completely randomized design with three repetitions, agronomic variables, grain yield and biomass were measured. An analysis of variance, Tukey’s mean comparison test (α≤ 0.05) were performed. The results show that the statistical parameters exhibit a wide diversity among the evaluated materials of native corns, in the values of the standard deviation in the agronomic attributes and biomass. The comparison of means of the variables shows that the white genotype produced the highest plant height, number of leaves, foliar area, total biomass and stover. White native corn obtained 44% more in stover production than the Hipopótamo hybrid. White corn generated the best characteristics for obtaining forage since it is a material of greater height, number of leaves, leaf area and total biomass, it also has the highest yield of the four native genotypes. The conclusion was that the genotype of white corn has the best characteristics for forage production.
Keywords: Zea mays L.; biomass; native; stover; yield